Análisis Financiero de la Cooperativa de Ahorro Y Crédito “CREDIAMIGO” Ltda. de la Ciudad de Loja Periodo 2014-2015. Propuesta de Mejoramiento - España Medina, Ivannova Michelle (2017)
The research paper called "FINANCIAL TO SAVINGS ANALYSIS AND COOPERATIVE CREDIT" CREDIAMIGO "LTDA. CITY OF LOJA 2014-2015. PROPOSAL FOR IMPROVEMENT "he was made in order to comply with the general objective is to conduct a financial analysis of the credit union" Crediamigo "Ltda. City of Loja period 2014-2015 by implementing indicators own industry to detect possible gaps and establish a proposal for improvement. That is why to achieve it was necessary to meet the specific objectives of analyzing financial statements through the horizontal and vertical method to know the financial situation - real economic cooperative, where it was determined that assets consist primarily portfolio credit liabilities obligations to the public with a decrease of 4.20% and 11.24% respectively by 2015; Y. heritage is right to support its current and future operations. In addition, apply financial indicators established by the regulator Superintendencia of Popular Economy and Solidarity, they helped deepen the information concerning: capital adequacy that efficiently supports fixed assets, portfolio unproductive, provisions and operating expenses; regarding the structure and asset quality shows a positive increase of 4.31%; the notable increase of 6.52% in delinquency rates on consumer and microcredit portfolios exhibit 5 conceived inefficient recovery of loans, a result the cooperative has increased its provisions; finally, liquidity indicators remain at a stable level. The development of the monitoring system PERLAS allowed to know that the cooperative has a satisfactory solvency, but does not meet the goals of provisions for loans over 12 months, the provision focuses more on loans from 1 to 12 months and not punishes the portfolio; effective financial structure is denoted that external loans exceed the set percentage from 0 to 5% with 5.28%; low asset financing committed by captured tanks contribution certificates; and in growth signals it shows the cooperative has grown satisfactorily in terms of its associates with 87.25% against its target of ≥ 15%. And finally to develop a proposal for improvement, three main lines of action with respect to managerial activities administrative directions, action steps against the credit portfolio and strategies to improve catchments, the same that seek to strengthen the profitability was determined.